Please turn on your cell phones: using pictures to explore the concept of culture in an Introductory Sociology course - Mauxion, Aurelien (TRAILS: Teaching Resources and Innovations Library for Sociology, 2016)
Realizing that most, if not all, students have direct access to a camera (their cell phone), and that cloud services allow digital pictures to be widely accessible, this activity proposes use of this simple technology to enhance an introductory class on culture. Students are asked to leave the classroom for five to ten minutes and take two pictures of things or events that they consider significant symbols of 1. American culture and 2. U.S. College culture. These pictures are instantly uploaded on a cloud service. The pictures are then available for the students to consult on their electronic device, discuss in small groups, and display on the classroom board when relevant to a general class discussion. This straightforward activity, from a logistical point of view, provides fresh and insightful material for a small-group workshop and class discussion. Students are especially engaged, as they are interested in explaining their choice. As the workshop transitions from small group to class discussion, the instructor takes notes and organizes on the board the main elements, dimensions, and possibilities offered by the concept of culture and other related sociological concepts. Wrapping up and synthesizing the information comes very naturally, as students literally co-produce the material for discussion.